2013
DOI: 10.1177/1753193413489639
|View full text |Cite
|
Sign up to set email alerts
|

Semi-occlusive dressing for the treatment of fingertip amputations with exposed bone: quantity and quality of soft-tissue regeneration

Abstract: Nineteen fingertip amputations with exposed bone were treated with a semi-occlusive dressing. The quantity and quality of the regenerated soft tissue was examined. In all 19 fingers there was sufficient uncomplicated healing such that secondary surgical procedures were not needed. At follow-up 6-18 months after the injury, soft tissue thickness around the bone of the distal phalanx measured 6.0 mm (SD 1.6) on the palmar aspect (opposite side 7.0 mm (SD 0.8)) and 4.2 mm (SD 1.7) distally (opposite side 4.5 mm (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 15 publications
2
49
0
7
Order By: Relevance
“…Secondarily healed finger pulp contour was recently shown to increase in length from 6 to 7 mm, as well as thickness (4.2 vs. 4.5 mm) to near-normal levels even when bone is exposed [13]. This likely occurs because the thick fat of the fingertip is pulled over the end of the bone by the glabrous skin as it contracts with secondary healing.…”
Section: Aesthetic Results Of Secondary Healingmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondarily healed finger pulp contour was recently shown to increase in length from 6 to 7 mm, as well as thickness (4.2 vs. 4.5 mm) to near-normal levels even when bone is exposed [13]. This likely occurs because the thick fat of the fingertip is pulled over the end of the bone by the glabrous skin as it contracts with secondary healing.…”
Section: Aesthetic Results Of Secondary Healingmentioning
confidence: 99%
“…Residual nail deformity was the usual cause of aesthetic dissatisfaction. In the total population of 1,592 fingertip amputations of our review, there were 100 reported nail deformities, (6 % of the fingertip injuries) [1,3,5,6,13,15,23,28,31].…”
Section: Aesthetic Results Of Secondary Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important feature of our treatment process is that secondary intention healing was applied to restore the skin defect of the nail unit during the period required for pathological re-examination. Several reports suggest secondary healing is better than skin grafting for fingertip amputation, resulting in good restoration of the original soft tissue thickness and sensation in the injured area 20 21 22 23 . In the skin defects of our patients, remarkable restoration of the nail folds and hyponychium was achieved with secondary intention healing during the re-evaluation period, almost to a degree that could be considered regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have revealed that rodents' digit tips are able to regenerate completely after amputation at the mid-level of the distal phalanx (7-9). It has also been observed that the fingertips of both adults and children can regenerate after injuries; nevertheless, the treatment protocol has not been standardized (10)(11)(12). We proposed that the one-stage wound healing of a fingertip injury could be achieved with application of artificial dermis treatment.…”
Section: Introductionmentioning
confidence: 99%